Review on Petri Net Modeling and Analysis of a Smartphone Manufacturing System. Issue 1 (1st January 2020) - Lin, Yi-Nan; Hsieh, Tsang-Yen; Yang, Cheng-Ying; Shen, Victor R.L.; Juang, Tony Tong-Ying; Huang, Ting-Jui
Abstract: Currently, the marketing strategy in the manufacturing industry is becoming more and more competitive. The emergence of lean production aims to reduce unnecessary wastes in the manufacturing processes. In order to achieve this goal, it is necessary to optimize manufacturing processes so as to reduce their costs. Therefore, reducing manufacturing costs has become the main developing direction people are now pursuing. The iPhone XS developed by Apple is now a popular product. To this end, this paper aims to describe its manufacturing system by using Petri nets, and to integrate the Prim algorithm with a minimum spanning tree (MST) to find the minimal cost path, achieving the goal of reducing the manufacturing costs. Two simulation software tools, WoPeD and PIPE, were applied to conduct the experiments. The experimental results have significantly indicated that the proposed approach is more feasible and acceptable than others.